2015
DOI: 10.1002/ps.4162
|View full text |Cite
|
Sign up to set email alerts
|

Non-target effects of commonly used plant protection products in roses on the predatory mite Euseius gallicus Kreiter & Tixier (Acari: Phytoseidae)

Abstract: Azadirachtin-A, acetamiprid, flonicamid, boscalid and kresoxim-methyl, cyprodinil + fludioxonil, dodemorph and fluopyram + tebuconazole were harmless for E. gallicus. Special attention should be paid to the impact of neonicotinoids and of acequinocyl and etoxazole, and to the application frequency with flonicamid on E. gallicus. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Phytoseiid mites (Acari: Phytoseiidae) are amongst the most important predators used in plant protection against arthropod pests such as spider mites, whiteflies and thrips 1–3 . Many species of commercially available phytoseiid mites are mass reared using astigmatid mites (Acari: Astigmata) as factitious prey 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoseiid mites (Acari: Phytoseiidae) are amongst the most important predators used in plant protection against arthropod pests such as spider mites, whiteflies and thrips 1–3 . Many species of commercially available phytoseiid mites are mass reared using astigmatid mites (Acari: Astigmata) as factitious prey 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…For the mass-rearing of N. cucumeris , the acaricid mite T. putrescentiae is used as factitious prey 21 . While some information on certain endosymbionts of N. cucumeris and T. putrescentiae 2,3 exists there is no information regarding the intrinsic microbiota of these species, or the effects of predatory-prey mite interactions on the ecology of these microbiota. Although mites are kept at high densities in mass rearing units it is still unclear whether both species share bacterial communities due to horizontal transfer via predation, contact or the feces 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The predatory mite E. gallicus is relatively new (Tixier et al 2010) and was found to occur on greenhouse rose plants (Döker et al 2014). In this crop it is now advised to use together with pollen for controlling thrips and whiteflies because of its good performance on pollen Put et al 2016). However, this study does not provide any evidence for better development on pollen on sweet pepper plants than the predatory mites A. swirskii and E. ovalis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we assessed which stages of E. americanus are attacked and killed by four species of phytoseiid predatory mites: (1) Amblyseius swirskii (Athias-Henriot) and (2) Amblydromalus limonicus (Garman and McGregor), both commercially available and effective predators of western flower thrips (Knapp et al 2013;Messelink et al 2006), (3) Euseius gallicus Kreiter and Tixier, recently commercialised and promoted to control thrips in roses in combination with pollen application Put et al 2016) and (4) Euseius ovalis (Evans), an effective predator of western flower thrips and whiteflies (Messelink et al 2008). Both the predation and oviposition rates of the predatory mites were assessed in the laboratory to evaluate which mite species is potentially the most effective predator of E. americanus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation